Abrasive wear in wear plates and hard coatings applied by welding with shielded electrode (2017)
Performance against abrasive wear was evaluated (in compliance with the ASTM G-65 standard) for both wear plates and hard coatings applied by electric welding. The characterization of the coatings was achieved by using hardness tests, optical microscopy and scanning electron microscopy (SEM). Although it was observed a direct correlation between hardness and wear resistance, a linear growth pattern was not followed. Besides the information from the hardness tests, data regarding the distribution and shape of the carbides in the welding bead are also necessary to choose the hard coating applied by welding, to protect against abrasive wear. Base metal and coatings had satisfactory joint, due to their dilution; the first welding layer had less hardness than the third welding layer.